The English Word Require: Its Meaning, Use, and Ideology - Utami, Ratna Anugrah Setyarini (Indonesian Journal of English Language Studies (IJELS), 2016)
The current study attempts to investigate the use and the meaning of the word require. This study also tries to find the ideology of the word require in the sentences or phrases. The data of the current study are derived through website Corpus of American Contemporary English. There are 100 data used for this research. The word require functions as a verb in every sentence or phrase.  All sentences or phrases which use the word require are analyzed to find the meaning of the word require. The findings show that the word require has four meanings: to have as a requisite or necessity; to stipulate as obligatory by the authority; to demand as obligatory or appropriateness;  and  to  impose an  obligation.  The most frequent  meaning occurs in the data is 39 % of which to have as a requisite or necessity. The rest is 38% of which to demand as obligatory or appropriateness; 14% of which to stipulate as obligatory by the authority; and only 9% of which to impose an obligation. The ideology of the word require is that the authority of institution has more power and people are powerless.  Keywords:  use, meaning, function, word, to require, ideology.